Design of the Security Analysis Mechanism with Complex Market Condition for Regional Power Grid - Huaiyu ZHANG; Hong HU; Lizi ZHANG; Chengpeng TANG; Yunjian LI; Xing JIA (Zhongguo dianli)
Security analysis is an important part of both the safe operation of regional power system and the normal operation of electricity market. At present regional electricity system in China has come to the complex situation with coexistence of regulation and deregulation, and interweaving of inter provincial transaction energy and planned electricity quantity, which compels the system operators to formulate corresponding security analysis mechanism. Firstly, this paper summarizes the power system security analysis mechanism for the single-mode market clearing and cross-market (country) electricity trading of foreign countries, and then explores the realistic basis, special constraints and requirements for regional power grid security analysis under the complex market environment in China. On this basis, a new security analysis mechanism framework adaptable to existing electricity market form, current power dispatching management system and regional power grid structure is designed, which includes the medium and long-term trans-province(region) electricity trading, day-ahead market pre-clearing generation plan of the pilot provinces and the day ahead generation plan of the non-pilot provinces. For the trans-province and trans-region medium and long-term transactions, this paper put forwards a power checking method based on the typical scenario set of cross-region transaction power curve and an improved security analysis mechanism scheme to elevate security analysis frequency. For the day-ahead period, it puts forward three alternative schemes adaptable to the complex market environment. Based on the comparative analysis, the implementation path of the scheme is proposed.